Revision ACL Reconstruction Indications and Technique - Marx, Robert G.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2014)
Although anterior cruciate ligament (ACL) reconstruction has a high success rate, a substantial number of patients are left with unsatisfactory results. Revision ACL Reconstruction: Indications and Technique provides detailed strategies for planning and executing revision ACL reconstructions. Concise chapters by a leading group of international orthopedic surgeons cover the diagnosis of failed ACL reconstruction, patient evaluation, preoperative planning for revision ACL surgery, and complex technical considerations.
Patient-related risk factors for ACL graft failure -- Avoiding the failed ACL: how to prevent ACL tears before they occur -- Diagnosis of failed ACL reconstruction -- Biomechanics and Etiology of ACL graft failure -- Technical causes of ACL graft failure -- Indications for revision ACL reconstruction -- Preoperative planning for revision ACL reconstruction -- Graft selection for revision ACL reconstruction -- How to handle a poorly placed femoral tunnel -- How to handle a poorly placed tibial tunnel -- Fixation in revision ACL reconstruction -- Single stage ACL revision reconstruction: indications and technique -- Two stage ACL revision: indications and technique -- Revising failed double-bundle ACL reconstruction -- The role of lateral extra-arcticular augmentation in revision ACL reconstruction -- Managing the infected ACL reconstruction -- Meniscus allograft transplantation in revision ACL reconstruction -- Cartilage surgery in revision ACL reconstruction -- Medial collateral ligament laxity in revision ACL reconstruction -- Posterolateral corner deficiency in revision ACL reconstruction -- Osteotomy for slope correction following failed ACL reconstruction -- Osteotomy for malalignment following failed ACL reconstruction -- Navigation for revision ACL reconstruction -- Approach to the multiply revised ACL knee -- Outcomes of revision ACL.
Keywords: Medicine; Orthopedics; Orthopedic surgery; Physical therapy; Sports medicine; Surgery; Endoscopic surgery; Medicine & Public Health; Orthopedics; Sports Medicine; Physiotherapy; Surgical Orthopedics; Surgery; Minimally Invasive Surgery